Comparación de los valores de glucosa en perros obtenidos a través de las dos técnicas de laboratorio Glucómetro y Espectrofotometría. - Macias Moreira, Suly Denise (2024)
The aim of this research is to compare glucose values in dogs using glucometer and spectrophotometry techniques at the HOSPIVET Veterinary Hospital. This experimental work aims to know the problem, in this way to examine and compare the blood glucose levels of different canines depending on the breed, sex and age and thus be able to find a solution for those affected and determine the normal glucose values in them. Normal blood glucose levels in dogs vary depending on the dog's age, breed, size, and health. Generally speaking, a dog's fasting blood sugar level should be between 70 and 110 mg/dL. If your dog has eaten recently, his blood sugar may be temporarily elevated. (Webb, 2023). Low blood glucose in a dog is called hypoglycemia. Hypoglycemia can occur if a dog doesn't eat enough, gets too much exercise, or is sick. Symptoms of hypoglycemia in dogs include weakness, tremors, irritability, disorientation, and seizures. If a dog is suspected of hypoglycemia, it should be taken to the vet immediately. (Álvarez-Linares, 2017). ). At the level of Ecuador in the city of Cuenca it is reported research carried out on blood glucose in dogs, in the present research it is reported that the analysis of glucose levels in the 30 cases studied using the methodology of spectrophotometry found a Pearson's coefficient of 0.014 and a coefficient of variation of 27%. The analysis of glucose levels using the rapid test using the glucometer with a Pearson's coefficient of 0.163 and a coefficient of variation of 24%. Table 3 and 3.1 show the average amount of glucose per male and female using the two methods studied, with females being higher in both cases.